Youth at Risk and the Writers in the Community Program : An Exploratory Evaluation - Hanley, Jill (The Centre for Literacy of Quebec (CFL), 2014)
Given its central importance to modern life, literacy has long been seen as both a challenge and an opportunity for members of marginalized populations (Movement for Canadian Literacy, 2001; Neuman, 2008), including youth at risk (Walker, Greenwood, Hart, & Carta, 1994; Willms, 1997). Such youth face many barriers to success at school and when they leave school with weak literacy skills, they face further challenges to employment and interaction with public institutions. On the other hand, helping youth at risk to develop stronger literacy skills – and, in the best case scenario, a love of reading and writing – may not only address practical challenges to future employment and public engagement (StatsCan, 2006) but can also make a significant contribution to positive self-esteem and positive relationships with their peers, teachers and parents (Chandler, 1999).

International Adult Skills Surveys: Andragogical Issues in Linguistic Minority Communities - Lurette, Donald (The Centre for Literacy of Quebec (CFL), 2014)
I have been working in the literacy field with francophone adults in a minority setting and in a variety of capacities for twenty years, and consider myself a reflective and critical practitioner. I strive to understand the world of adult education and skills development based on my practical experiences and observations from the field. This text is written from that perspective, based on principles of andragogy. Using inductive and deductive processes, I propose ideas and reflections on the concept of the evaluation of basic skills of adults living in linguistic minority communities in Canada. On the theoretical side, I use several key studies, including an analytical background paper written for The Centre for Literacy’s 2013 Summer Institute by Jean-Pierre Jeantheau, Chargé de mission national of the French Agence nationale de lutte contre l'illettrisme, on the subject of linguistic minority groups and international literacy assessments.

Annual Activity Report : June 1, 2013 - May 31, 2014 - Literacy Quebec (LQ) (2014)

PACTE Project 2013-2014 : The Power of an Online Presence, a Skill to be Harnessed. - Literacy Quebec (LQ) (2014)
The following project has been completed by Literacy Quebec by a grant from Opération Projets PACTE As a provincial organization, Literacy Quebec’s mandate is to support community-based literacy organizations that provide service to English-speaking adults in Quebec, through training, networking and professional development.

Western Quebec Literacy Council: Annual Report: 2013-2014 - Western Quebec Literacy Council (2014)